(untitled) (Journal of Contemporary Studies, 2019)
Abstract U.S failure in Afghanistan may have many reasons but most striking is US inability to create a political Afghanistan in parallel with a military Afghanistan. The political strategy in Afghanistan was over-shadowed by military strategy. All the U.S force commanders in Afghanistan looked at Afghanistan not as a political but as a military problem. These generals remained very passionate about the military strategies geared to win the war in Afghanistan. This paper tries to determine why the achievement of the political aims of fighting the war in Afghanistan remained subservient to the achievement of the military aims; and secondly, now that the American focus is on pursuing a political settlement in Afghanistan, how likely is the U.S to achieve this aim? Which are the likely scenarios that can develop in the coming days and how will they affect interests of various actors involved in the Afghan war and its end game?